Macroeconomic Developments in Low-Income Developing Countries : 2014 Report. (Policy Papers; Policy Paper, 2014)
This report examines macroeconomic developments and related vulnerabilities in low-income developing countries (LIDCs)-a group of 60 countries that have markedly different economic features to higher income countries and are eligible for concessional financing from both the IMF and the World Bank. Collectively, they account for about one-fifth of the world's Population.